An improved Wu-Manber multiple patterns matching algorithm - Weifeng Zhang (2016 IEEE International Conference on Electronic Information and Communication Technology (ICEICT), 2016)
Protocol identification is an important step in information countermeasures. As a key technique in protocol identification, pattern matching algorithms aim to find the feature bit patterns of target protocol in bit stream. Traditional pattern matching algorithms are not accomplished in matching bit patterns. This paper proposed an multiple patterns matching algorithm based on the classical Wu-Manber algorithm. The proposed algorithm can improve the insufficient of the WM when dealing bit stream. The effectiveness of our improved algorithm is verified by a series of experiments.